Where does allogeneic stem cell transplantation fit in the treatment of chronic lymphocytic leukemia? - Dreger, Peter; Montserrat, Emili (Current hematologic malignancy reports, 2015)
Allogeneic hematopoietic stem cell transplantation (alloHSCT) has been considered as the treatment of choice for patients with high-risk chronic lymphocytic leukemia (CLL) (i.e., refractory to purine analogs, short response (<24 months) to intensive treatments, and/or presence of 17p/TP53 abnormalities). Currently, new and highly effective therapeutic agents targeting BCR-mediated intracellular signal transduction have been incorporated into the CLL treatment armamentarium. These signal transduction inhibitors (STI) will change the algorithms of high-risk CLL (HR-CLL) management. Despite the limited body of evidence, there is sufficient rationale for withholding alloHSCT in patients with 17p-/TP53mut CLL in first remission. In contrast, the perspectives of patients with relapsed 17p-/TP53mut CLL remain uncertain even if responding to STI. The same accounts for patients with HR-CLL progressing under STI. In both scenarios, it is reasonable to consider alloHSCT, ideally after response to alternative STI regimens.